Evaluation of a detomidine–ketamine–azaperone combination for the chemical immobilization of fallow deer (Dama dama) - De Benedictis, Giulia Maria; Baggio, Alice; Pesaro, Stefano; Magnone, William; Miani, Giovanna; Andolfatto, Alice; Bono, Lucia; Zanusso, Francesca (Frontiers in Veterinary Science, 2025)
The fallow deer (Dama dama) is a widely distributed cervid in Europe, often managed in enclosed settings for conservation, education, or hunting purposes. Chemical immobilization is frequently required during routine handling; however, fallow deer remain understudied in the scientific literature with regard to standardized anesthetic protocols. This study aimed to evaluate the efficacy and safety of an anesthetic protocol combining detomidine (0.2 mg/kg), ketamine (2 mg/kg), and azaperone (0.3 mg/kg) in 22 captive fallow deer. Animals were immobilized for clinical procedures, including health checks, blood sampling, individual identification, and translocation. The quality of anesthesia and physiological parameters (heart rate, respiratory rate, oxygen saturation, end-tidal CO2, arterial blood pressure, temperature) were monitored throughout immobilization. Anesthetic depth was evaluated through the assessment of reflexes, muscle tone, and eye position. The quality of induction, immobilization at approach, and recovery were systematically evaluated using dedicated scoring systems. Induction was smooth in all animals, with lateral recumbency time, and time to first safe approach achieved in 10.7 ± 6.4 min, and 22.0 ± 5.1 min, respectively. Mean handling time was 49.8 ± 9.6 min. Physiological parameters remained within acceptable limits, with only transient hypoxemia. Recovery was uneventful in most individuals, with the majority exhibiting good to excellent recovery quality and standing within 20 min of atipamezole administration. Only one individual experienced a poor-quality and prolonged recovery. No complications were observed post-procedure. The detomidine-ketamine-azaperone combination proved to be an effective and safe protocol for immobilizing fallow deer, providing stable anesthesia and good recovery quality. Dedicated scoring systems enabled a standardized and repeatable evaluation of the quality of the used protocol and its suitability. This study is the first to describe the use of azaperone in combination with detomidine and ketamine in fallow deer, contributing new insights into non-opioid immobilization strategies for cervids.